The Impact Of Enterprise Risk Management, Corporate Social Responsibility, And Sustainability Report On Firm Value In Banking Sector Of Indonesia, Malaysia, And Thailand (Vallis Aurea, 2022)
The purpose of this research was to determine the impact of disclosure on enterprise risk management (ERM), corporate social responsibility (CSR), and sustainability reports (SR) on firm value. Data for this research is taken from financial reports, annualreports, and reports issued by firms. In this study, the sample used was banking firms listed on Indonesia, Malaysia, and Thailand Stock Exchanges from 2019-2020. Sampling using purposive sampling technique with four criteria. Firms that meet these criteria are 36 Indonesian firms, 10 Malaysian firms, and 8 Thai firms. The method of data analysis is multiple regression analysis using the Eviews software. The results show that Enterprise Risk Management positively influences firm value. Meanwhile, the Corporate Social Responsibility and Sustainability Report has no effecton banking firm's value. The results of this study can be used as a reference for potential investors to know the condition of each company they want to invest in.